PENGARUH KEPEMIMPINAN, PENGAWASAN DAN SANKSI HUKUMAN TERHADAP KEDISIPLINAN KERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA BIMA - SYAHRIAL NURYADIN (Master of Management, Mataram University, 2016)
This study aimed to analyze the influence of leadership, supervision systems and punitive sanctions against the level of employee discipline in the Regional Secretariat Bima. There are three independent variables in this study; leadership, supervision, and punitive sanction against the level of employee discipline. In this study population is 240 people with a sample of 100 respondens selected by the simple random sampling. Simultaneously the results of the study concluded that leadership variable have an influence on work discipline but not significant, control variable have an influence on work discipline but not significant and punitive sanctions variable positive and significant impact on employee discipline. Punitive sanctions is a variable that has the most dominant influence compared with other variables. Of the research results can be recommended a few things, that isemployee discipline would be improved if good leadership, good supervision and sanctions fair punishment can be combined and synchronized with well by the leadership, either in the form of rules written and in it’s application. Keyword : Leadership, Supervision, Sanction, Employee Disciplin